Antioxidant activity-guided isolation of flavonoids from Silene gallica aerial parts. (August 2022) - Bechkri, Sara; Magid, Abdulmagid Alabdul; Khalfallah, Assia; Voutquenne-Nazabadioko, Laurence; Kabouche, Ahmed; Sayagh, Charlotte; Harakat, Dominique; Kabouche, Zahia
Abstract: A bio-guided fractionation of the 80% aqueous ethanolic extract of the aerial parts of Silene gallica L. (Caryophyllaceae), growing in North-Eastern Algeria, was performed to evaluate its antioxidant activity using DPPH, hydroxyl radical scavenging and CUPRAC assays. Successive chromatographic separations of the most antioxidant n -BuOH soluble fraction yielded four acylated flavone C -glycosides, vitexin 2''- O - β -d -(4''', 6'''-di-acetyl)-glucopyranoside (1 ), orientin-2''- O - β -d -(4''', 6'''-di-acetyl)-glucopyranoside (2 ), orientin-2''- O - β -d -(6'''-feruloyl)-glucopyranoside (3 ), and orientin-2''- O - β -d -(6'''-sinapoyl)-glucopyranoside (4 ), as well as six known compounds including four flavonoids (5 -8 ), a phenylpropanoid glycerolglucoside (regaloside A) (9 ), and a phytoecdysteroide (20-hydroxyecdysone) (10 ). Their structures were established by UV, 1D, 2 D NMR, and HR-ESI-MS spectral data, in addition to comparison with literature data. The antioxidant activity of the crude extracts, fractions and compounds 1 -8 was evaluated. Two acylated orientin glycosides (3 and 4 ) displayed the strongest antioxidant activity. Graphical Abstract: ga1 Highlights: Bio-guided fractionation of the 80% aqueous ethanolic extract of the aerial parts of Silene gallica L. was used. Four acylated flavone C -glycosides were identified in the most antioxidant n -BuOH soluble fraction. The structures of isolated compounds were elucidated by NMR and HR-ESI-MS analyses The antioxidant activity of the crude extracts, fractions and compounds was evaluated Two acylated orientin glycosides displayed the strongest antioxidant activity.